2003
DOI: 10.1111/j.1365-2621.2003.tb09662.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Streptococcus mutans Growth by Hen Egg‐derived Fatty Acids

Abstract: Hen egg yolk contains significant antibacterial activity. We show that this activity is associated with the release of free fatty acids. Chloroform-methanol extraction on egg yolk demonstrated the activity to be lipoprotein-bound before enzymatic digestion and associated with the lipid-soluble chloroform phase afterward. Acetone extraction yielded a fraction of egg yolk, which was 97% triglyceride and highly antibacterial to Streptococcus mutans when treated with pancreatin. The fatty acid profile of the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that intakes of EY may increase the risks of CVDs ascribed to high levels of cholesterol and saturated fatty acids, resulting in supplement deficiency for consumers . Anyway, recent reports indicate that there is no association between proper intakes of eggs in healthy people and CVDs. , On the contrary, EY and its components possess numerous physiological benefits, particularly regarding anti-inflammatory, antimicrobial, and antioxidant activities, protecting eyesight, and improving memory. , It is well-known that phospholipids (PLs) and choline are essential for nervous system structural and functional integrity . EY is just a valuable source of PLs and choline .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that intakes of EY may increase the risks of CVDs ascribed to high levels of cholesterol and saturated fatty acids, resulting in supplement deficiency for consumers . Anyway, recent reports indicate that there is no association between proper intakes of eggs in healthy people and CVDs. , On the contrary, EY and its components possess numerous physiological benefits, particularly regarding anti-inflammatory, antimicrobial, and antioxidant activities, protecting eyesight, and improving memory. , It is well-known that phospholipids (PLs) and choline are essential for nervous system structural and functional integrity . EY is just a valuable source of PLs and choline .…”
Section: Introductionmentioning
confidence: 99%
“…Minimum inhibitory concentration (MIC) of the extracts was studied by using a previously reported 96-well microtiter plate assay (Brady et al, 2003). The microtiter plate-based assay allowed bacterial growth at 30°C and its inhibition to be assessed over time.…”
Section: Antimicrobial Assaysmentioning
confidence: 99%
“…Natural antibiotic agents from various medicinal plants and food materials have recently been investigated as promising agents to prevent dental caries (Katsura and others 2001; Hwang and others 2004; Bakri and Douglas 2005). Hen‐egg yolk, bacteriocin, and chitosan have been reported to significantly inhibit the growth of S. mutans (Brady and others 2002, 2003; Oh and others 2003; Hayashi and others 2007). Several polyphenols in the green tea extracts such as catechin, epicatechin, gallocatechin, epigallocatechin, and so on, inhibit the growth of oral pathogens (Otake and others 1991).…”
Section: Introductionmentioning
confidence: 99%